Drug shortage in Egypt: causes and mitigation measures - Saad, Abeer Alanwar (AUC Knowledge Fountain, 2019)
Drug shortage is a worldwide problem, which gained the attention of many authorities in recent years including the Egyptian government. The problem has markedly increased in Egypt during the past few years and has had a significant negative impact on patient care with subsequent costly financial implications. Despite the importance of the drug shortage problem and its consequences on the health of Egyptians and society as a whole, only a few researchers have addressed the topic in Egypt. This qualitative study aims at filling the gap and providing a better understanding of the problem in the Egyptian context. To achieve the study objective, the root causes of the problem and the actions taken by the government to mitigate the problem are explored. In-depth, semi-structured interviews are carried out with different stakeholders including from government, industry, distributors, and pharmacies. The findings of this research revealed that the drug shortage is attributed to a myriad of interlinked causes. The most critical causes of drug shortages are as follows: the drug pricing constraints, the devaluation, economic changes, overdependence on the importation of production inputs, illegal distribution practices, excessive bureaucracy and complicated procedures, manufacturing problems, poor supply chain management, and scarcity of raw materials. The findings also show that although the government has exerted many efforts to tackle drug shortages, there is still a gap to be addressed. Based on experiences of other countries and according to the Egyptian context, solutions are proposed to help in mitigating drug shortages in Egypt which include enhancing the sustainability of the production of medicines by improving companies’ profitability, improving collaboration between various stakeholders, developing a system for reporting and communication of drug shortage information, and modifying workflow within MoHP to avoid unnecessary delays.